1962
DOI: 10.1039/tf9625801768
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of the hydrogen + oxygen reaction by formaldehyde

Abstract: The inhibiting action of HCHO on the first and second limits of the H2+02 reaction has been studied in KClcoated vessels at 540°C. The e5ciency of inhibition is almost inversely proportional to the mole fraction of 0 2 , and is less dependent on the mole fraction of H2. This indicates that the main primary termination process is thereaction H+HCH0( 14) which competes with the reaction H+02(2); a smaller contribution results from the reaction of OH+HCHO(lS) competing with OH+H2(1), or from O+HCHO = OHSHCO(13) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1966
1966
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…For the CH 2 O + H reaction, direct H atom abstraction producing CHO + H 2 , several kinetic experiments have been carried out in different temperature ranges in the past decade. In 1999, Baulch et al recommended the rate constant expression for the temperature range 300–1700 K, k = 2.1 × 10 –16 T 1.62 exp­[−1090/ T ] cm 3 molecule –1 s –1 , derived by Choudhury and Lin from a nonlinear least-squares analysis of their high-temperature shock tube data with the low-temperature data of Baldwin and Cowe, Westenberg and deHaas, Ridley et al, and Klemm . Dóbé et al reported a rate constant at 298 K, (3.98 ± 0.83) × 10 –14 cm 3 molecule –1 s –1 , measured by the discharge flow technique.…”
Section: Introductionmentioning
confidence: 99%
“…For the CH 2 O + H reaction, direct H atom abstraction producing CHO + H 2 , several kinetic experiments have been carried out in different temperature ranges in the past decade. In 1999, Baulch et al recommended the rate constant expression for the temperature range 300–1700 K, k = 2.1 × 10 –16 T 1.62 exp­[−1090/ T ] cm 3 molecule –1 s –1 , derived by Choudhury and Lin from a nonlinear least-squares analysis of their high-temperature shock tube data with the low-temperature data of Baldwin and Cowe, Westenberg and deHaas, Ridley et al, and Klemm . Dóbé et al reported a rate constant at 298 K, (3.98 ± 0.83) × 10 –14 cm 3 molecule –1 s –1 , measured by the discharge flow technique.…”
Section: Introductionmentioning
confidence: 99%
“…The authors acknowledge based on past experience that the relatively more accurate polarization configuration interaction computed barrier of 12.7 kcal/mol was probably too high by up to several kilocalories/mole. Harding and Schatz also performed TST calculations using generalized valence bond configuration interaction derived parameters, having to reduce the computed barrier height to 4.9 kcal/mol in order to reconcile the computed rates with available experimental data for the title reaction. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Harding and Schatz also performed TST calculations using generalized valence bond configuration interaction derived parameters, having to reduce the computed barrier height to 4.9 kcal/mol in order to reconcile the computed rates with available experimental data for the title reaction. 17,30,31 More recently, Irdam et al in the 1990s recomputed the potential energy surface of this system with a multireference configuration interaction scheme, 20 employing a moderately sized pVDZ basis set. The authors obtained a barrier height of 12.8 kcal/mol, still too high to fit experimental data, by about a factor of 2.…”
Section: Introductionmentioning
confidence: 99%
“…(b) By assuming that removal of H atoms is the important primary inhibition process but that Q decreases as the pressure is lowered. Further observations on the way in which Q varies with pressure may be obtained by a study of the inhibiting action of C2H4 at the first limit which, as shown with HCHO 15 and C2H& 4 enables the pressure range to be extended. Simple equations for the inhibition of the first limit may be derived by making the following assumptions: where k H is the velocity constant for the surface destruction of H atoms and Ql is the fraction of radicals produced from C2H4 which are destroyed without propagating the chain at first limit pressures PI.…”
Section: Discussionmentioning
confidence: 99%